Ga-Fe-based liquid alloy catalyst as well as preparation method and application thereof

The effective synthesis of ammonia under low temperature and low pressure conditions by Ga-Fe-based liquid alloy catalysts, which solves the problems of energy consumption and environmental pollution under high temperature and high pressure conditions in the prior art, and improves the activity and stability of the catalyst.

CN119746872AActive Publication Date: 2025-04-04HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202510077859.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-04
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The prior art requires high temperature and high pressure conditions when synthesizing ammonia with thermal catalytic results, resulting in energy consumption and environmental pollution problems, and the active sites of traditional catalysts are prone to poisoning and inactivation.

Method used

Ga-Fe-based liquid alloy catalyst is used to form a low melting point alloy by mutually dissolved by metal Ga and Fe and M (such as Ti, Mn, Co, Ni, etc.), so that the catalyst becomes liquid at the reaction temperature, improve the contact efficiency of nitrogen and hydrogen with metals Fe and M, and adjust the electronic structure of the catalyst through the strong and weak interaction between Fe and M.

Benefits of technology

The effective synthesis of ammonia under low temperature and low pressure conditions is achieved, which reduces energy consumption and environmental pollution, avoids the problem of inactivation of active sites, and improves the activity and stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746872A_ABST
    Figure CN119746872A_ABST
Patent Text Reader

Abstract

The invention relates to a Ga-Fe-based liquid alloy catalyst and a preparation method and application thereof, the Ga-Fe-based liquid alloy catalyst comprises a metal Ga, a metal Fe and a metal M, and the metal M is one of Ti, Mn, Co, Ni, Cu, Zr, Nb, Mo and W. According to the Ga-Fe-based liquid alloy catalyst provided by the invention, the metal Ga is taken as a matrix, the metal Fe and the metal M are taken as active catalytic sites, and based on the characteristic that the metal Ga can be mutually dissolved with other metals to form a low-melting-point alloy, the formed alloy catalyst can be changed into a liquid state for reaction at a reaction temperature, and due to the characteristic of liquidity of the liquid state, the alloy catalyst has good catalytic activity. The metal active components of ammonia synthesis can be continuously refreshed at the interface, so that nitrogen and hydrogen are more fully contacted with metal Fe and metal M, the mass transfer efficiency is higher, the phenomenon that active sites of a traditional solid catalyst are poisoned and inactivated is avoided, and N2 and H2 can effectively react to generate ammonia under the low-temperature and low-pressure conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of thermal catalysis technology, and in particular to a Ga-Fe based liquid alloy catalyst and a preparation method and application thereof. Background Art

[0002] The importance of ammonia is self-evident. It plays an irreplaceable role in agricultural production, military medical treatment, energy application, etc. Research on thermal catalytic synthesis of ammonia has never stopped for more than 100 years. However, the CO2 produced in industrial production over the years has caused a serious greenhouse effect, and the problem of energy consumption cannot be ignored. Under the dual carbon goals and the development concept of green chemistry, ammonia synthesis under low temperature and low pressure conditions is a field worthy of research, which can effectively reduce the dual burden of energy and environment.

[0003] Under this premise, liquid alloys have entered the field of vision of researchers, especially Ga-based liquid alloys. There have been many related studies, such as: Unveiling metal mobility in a liquid Cu-Ga catalyst for ammonia synthesis and Conversion of CO2 into fibrous carbon materials using Ga-based liquid alloys and Gallium-rich Pd-Ga phases as supported liquid metal catalysts, etc. Liquid alloy catalysts do not rely on precious metals, which reduces costs and meets the needs of sustainable development. This is crucial to reducing dependence on rare and expensive resources. Liquid alloy catalysts show higher activity and stability than traditional catalysts in some cases. For example, Cu-Ga liquid alloy catalysts show 100 hours of stability in thermal catalytic synthesis of ammonia. In addition, liquid metal catalysts may subvert traditional chemical engineering processes due to their unique mobility and high catalytic surface area, especially in the fields of manufacturing plastics, fertilizers, fuels, etc. Green chemical solutions: Liquid metal catalysts provide a possible "green chemical" solution, which helps to reduce energy consumption in the chemical industry and promote green chemical reactions.

[0004] For example, the patent with publication number CN112266002A discloses a method for catalytic synthesis of ammonia under normal pressure, in which hydrogen and nitrogen are used in a reactor to synthesize ammonia under normal pressure with a liquid alloy as a catalyst. In this method, the liquid alloy preparation method is as follows: in an argon glove box, Li and Sn are mixed and placed in a crucible; LiCl and KCl are mixed and covered on the surface to isolate the metal from the atmosphere; the crucible is transferred as a whole to a tubular furnace, heated to under argon protective gas, and after insulation, cooled to room temperature, and LiCl and KCl are removed to obtain a prefabricated Li-Sn alloy; and the liquid alloy prepared by this method still needs to use molten salt when catalytically synthesizing ammonia. This liquid alloy uses highly active alkali metals, which react easily with nitrogen to form alkali metal nitrides, and uses molten salts to provide a new reaction interface for the metal nitrides to react with hydrogen to synthesize ammonia, so that the metal nitrides continuously generate ammonia. The generated first metal nitride then reacts with hydrogen to synthesize ammonia, and then the second metal and the third metal are used to catalyze the decomposition of the first metal hydride into the first metal and hydrogen. However, this method requires synthesis with the help of molten salts under inert gas conditions, and has high requirements for equipment and methods. Summary of the invention

[0005] Based on this, the purpose of the present invention is to provide a Ga-Fe-based liquid alloy catalyst and its preparation method and application. The Ga-Fe-based liquid alloy catalyst uses metal Ga as a matrix and metal Fe and metal M as active catalytic sites, so that N2 and H2 can effectively react to generate ammonia under low temperature and low pressure conditions.

[0006] To achieve the above object, the present invention adopts the following technical solutions: The present invention first provides a Ga-Fe-based liquid alloy catalyst, which includes metal Ga, metal Fe and metal M, and the metal M is one of Ti, Mn, Co, Ni, Cu, Zr, Nb, Mo, and W.

[0007] The Ga-Fe-based liquid alloy catalyst provided by the present invention uses metal Ga as a matrix and metal Fe and metal M as active catalytic sites. Based on the property that metal Ga can be mutually dissolved with other metals to form a low-melting-point alloy, the formed alloy catalyst can be transformed into a liquid state at a reaction temperature for reaction. Since the liquid state has the characteristic of fluidity, it is beneficial for the metal active components of synthetic ammonia to be continuously refreshed at the interface, so that nitrogen and hydrogen are in more complete contact with metal Fe and metal M, and the mass transfer efficiency is higher. The phenomenon of poisoning and deactivation of the active sites of traditional solid catalysts will not occur, so that N2 and H2 can react effectively to generate ammonia under low temperature and low pressure conditions. In addition, the metal Fe and the metal M can interact with each other in a strong and weak manner, so that the electronic structure of the catalyst can be adjusted, and then the activity and selectivity of the synthetic ammonia reaction can be adjusted.

[0008] As a further improvement of the above solution of the present invention, in the Ga-Fe-based liquid alloy catalyst, the mass percentage of the metal Ga is 90% to 99%; And / or, in the Ga-Fe based liquid alloy catalyst, the mass ratio of the metal Fe to the metal M is 1-2:1.

[0009] The present invention also provides a method for preparing the Ga-Fe based liquid alloy catalyst as described above, which comprises the following steps: under a protective atmosphere, adding metal Ga powder, metal Fe powder and metal M powder into a ball milling jar and sealing it, and ball milling it in a sealed state to obtain a Ga-Fe based liquid alloy catalyst.

[0010] As a further improvement of the above scheme of the present invention, the ball-to-material ratio of the ball mill is 20-30:1, the rotation speed is 200-600 rpm, and the time is 10-60 min.

[0011] As a further improvement of the above solution of the present invention, the protective atmosphere is in a N2 or Ar glove box.

[0012] As a further improvement of the above solution of the present invention, the purity of the metal Ga powder and the metal Fe powder is 99.99%.

[0013] The present invention also provides a use of the Ga-Fe based liquid alloy catalyst as described above in thermal catalytic synthesis of ammonia.

[0014] As a further improvement of the above scheme of the present invention, it includes the following steps: loading the Ga-Fe-based liquid alloy catalyst at one end of the U-shaped reaction tube with a sieve plate of the synthetic ammonia fixed reaction bed, introducing a mixed gas of N2 and H2, and heating the reaction.

[0015] As a further improvement of the above scheme of the present invention, in the mixed gas, the molar ratio of N2 to H2 is 1:1~5, and the flow rate of the mixed gas is 20~300mL / min.

[0016] As a further improvement of the above scheme of the present invention, the temperature of the heating reaction is 200~500°C and the pressure is 1~5MPa.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The Ga-Fe-based liquid alloy catalyst provided by the present invention uses metal Ga as a matrix and metal Fe and metal M as active catalytic sites. Based on the property that metal Ga can be mutually dissolved with other metals to form a low-melting-point alloy, the formed alloy catalyst can be converted into a liquid state for reaction at the reaction temperature. Since the liquid state has the characteristic of fluidity, it is beneficial for the metal active components of synthetic ammonia to be continuously refreshed at the interface, so that nitrogen and hydrogen are in more complete contact with metal Fe and metal M, and the mass transfer efficiency is higher. The phenomenon of poisoning and deactivation of the active sites of traditional solid catalysts will not occur, so that N2 and H2 can react effectively to generate ammonia under low temperature and low pressure conditions; and the metal Fe and metal M can interact with each other in a strong and weak manner, which can adjust the electronic structure of the catalyst, and then adjust the activity and selectivity of the synthetic ammonia reaction.

[0018] 2. During the preparation of the Ga-Fe-based liquid alloy catalyst of the present invention, inert gas protection is used to prevent oxidation, and the Ga-Fe-based liquid alloy is synthesized simply and quickly by ball milling. The metal Ga powder, metal Fe powder and metal M powder can be fully mixed by ball milling, and the grinding medium and metal material in the ball mill jar are caused to collide and rub against each other by rotation and vibration, thereby significantly reducing the size of the material particles and increasing the surface area of ​​the particles, which is beneficial to improving the activity and availability of the catalyst; the high-energy impact and local high temperature during the ball milling process can promote the solid-state reaction, making the alloying process between Ga, Fe and M more thorough; through appropriate ball milling conditions, a catalyst with nanometer size, high surface area and unique physical and chemical properties can be obtained. The preparation method of the present invention is simple to operate, highly repeatable, and can be prepared in large quantities.

[0019] 3. The Ga-Fe-based liquid alloy synthesized in the present invention is used as a thermal catalytic ammonia synthesis catalyst, which can achieve good catalytic effect under low temperature and low pressure conditions. During the reaction, the liquid alloy is constantly turned over by the action of the airflow, which is beneficial to the refreshing of the active components at the interface, thereby avoiding the deactivation of the reaction sites, ensuring good reaction activity and cycle stability, and facilitating large-scale synthesis of ammonia. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Ga prepared in Example 1 of the present invention 95 XRD pattern of Fe3Ni2 liquid alloy; Figure 2 Ga prepared in Example 1 of the present invention 95 SEM and Mapping images of Fe3Ni2 liquid alloy; Figure 3 Ga prepared in Example 2 of the present invention 90 SEM and mapping images of Fe6Co4 liquid alloy. DETAILED DESCRIPTION

[0021] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0023] Example 1 This embodiment provides a Ga-Fe based liquid alloy catalyst, and the preparation method thereof comprises the following steps: in a glove box filled with N2, 1.9 g of Ga powder, 0.06 g of Fe powder and 0.04 g of Ni powder are weighed and placed in a polytetrafluoroethylene grinding jar, the mass ratio of grinding balls to materials is 30:1, the grinding jar is sealed, and ball milling is performed for 30 minutes under N2 protection to obtain a Ga-Fe based liquid alloy catalyst Ga 95 Fe3Ni2.

[0024] Figure 1 The Ga prepared in this example 95 The X-ray diffraction spectrum of Fe3Ni2 liquid alloy obtained by XRD characterization (XRD, Cu-Kα, λ=1.5406Å) is Figure 1 It can be seen that the Ga prepared in this embodiment 95 Fe3Ni2 has good crystallinity, corresponding to the standard cards (Ga PDF#05-0601), (Fe PDF#85-1410), and (Ni PDF#87-0712), respectively.

[0025] Figure 2 The Ga prepared in this example 95 Fe3Ni2 liquid alloy was characterized by scanning electron microscopy to obtain scanning electron microscope photos and element distribution maps. Figure 2 It can be seen that the Ga prepared in this embodiment 95 Fe3Ni2 is solid particles at room temperature, and the Ga, Fe and Ni elements are distributed very evenly.

[0026] Comparative Example 1 This comparative example proposes a liquid alloy catalyst, and the preparation method thereof comprises the following steps: in a glove box filled with N2, 1.94 g of Ga powder and 0.06 g of Fe powder are weighed and placed in a polytetrafluoroethylene grinding jar, the mass ratio of grinding balls to materials is 30:1, the grinding jar is sealed, and ball milling is performed for 30 minutes under N2 protection to obtain a liquid alloy catalyst Ga 97 Fe3.

[0027] Comparative Example 2 This comparative example proposes a liquid alloy catalyst, and the preparation method thereof comprises the following steps: in a glove box filled with N2, 1.96 g of Ga powder and 0.04 g of Ni powder are weighed and placed in a polytetrafluoroethylene grinding jar, the mass ratio of grinding balls to materials is 30:1, the grinding jar is sealed, and ball milling is performed for 30 minutes under N2 protection to obtain a Ga-Fe-based liquid alloy catalyst Ga 98 Ni2.

[0028] Test Example 1 This test example tests the catalytic activity of the liquid alloy catalysts of Example 1 and Comparative Examples 1-2 as thermal catalytic ammonia synthesis catalysts, wherein the method for thermal catalytic ammonia synthesis is: 500 mg of the catalyst is loaded into one end of the U-shaped reaction tube with a sieve plate of a fixed-bed reactor for ammonia synthesis, the reaction temperature is fixed at 400°C, the reaction pressure is 3 MPa, the molar ratio of N2:H2 is 1:3, the flow rate of the mixed gas is 120 mL / min, the generated ammonia is collected and the ammonia yield is calculated. The results are shown in Table 1.

[0029] The ammonia yield is calculated as follows: the collected ammonia is passed into a H2SO4 solution (0.1 mol / L), and NH3 is converted into NH4 in the acid solution. + , using UV spectrophotometer to calculate NH4 in H2SO4 solution + The specific method is salicylic acid-hypochlorite spectrophotometry. The specific principle is that in the presence of alkaline medium (pH=11.7) and sodium nitrosoferricyanide, ammonia and ammonium ions in water react with salicylate and hypochlorite ions to generate a blue compound with a maximum absorption peak at 697 nm. The absorbance is measured by a spectrophotometer to quantitatively analyze the concentration of ammonia. NH4Cl is used as NH4 + The standard substance is used to prepare NH4Cl solutions of different concentrations. According to the above salicylic acid-hypochlorite spectrophotometry, a NH4 + Concentration-absorbance standard curve; the H2SO4 solution after absorbing ammonia is tested with the same test method as the standard curve and substituted into the standard curve to obtain the NH4 in the H2SO4 solution. + Concentration. Then calculate the ammonia yield according to the following formula:

[0030] Where: Represents NH4 during reaction time + The concentration difference, represents the mass of the catalyst, t Represents reaction time.

[0031] Table 1 Test results of the catalytic reaction activity of synthetic ammonia in Example 1 and Comparative Examples 1-2

[0032] From the results in Table 1, it can be seen that compared with the single metal modified Ga liquid alloy Ga 98 Ni2 and Ga 97 Fe3, bimetallic modified Ga liquid alloy Ga prepared in Example 1 95 Fe3Ni2 has a good ammonia synthesis reaction rate and a significant improvement in activity.

[0033] Example 2 This embodiment provides a Ga-Fe based liquid alloy catalyst, and the preparation method thereof comprises the following steps: in a glove box filled with N2, 1.8 g of Ga powder, 0.12 g of Fe powder and 0.08 g of Co powder are weighed and placed in a polytetrafluoroethylene grinding jar, the mass ratio of grinding balls to materials is 30:1, the grinding jar is sealed, and ball milling is performed for 40 minutes under N2 protection to obtain a Ga-Fe based liquid alloy catalyst Ga 90 Fe6Co4.

[0034] Figure 3 The Ga prepared in this example 90 The Fe6Co4 liquid alloy was characterized by scanning electron microscopy to obtain scanning electron microscope photos and element distribution maps. Figure 3 It can be seen that the Ga prepared in this embodiment 90 Fe6Co4 is a solid particle at room temperature, and the Ga, Fe, and Co elements are distributed very evenly.

[0035] Comparative Example 3 This comparative example proposes a liquid alloy catalyst, and its preparation method comprises the following steps: in a glove box filled with N2, 1.88g of Ga powder and 0.12g of Fe powder are weighed and placed in a polytetrafluoroethylene grinding jar, the mass ratio of grinding balls to materials is 30:1, the grinding jar is sealed, and ball milling is performed for 40 minutes under N2 protection to obtain Ga 94 Fe6.

[0036] Comparative Example 4 This comparative example proposes a liquid alloy catalyst, and its preparation method comprises the following steps: in a glove box filled with N2, 1.92g of Ga powder and 0.08g of Co powder are weighed and placed in a polytetrafluoroethylene grinding jar, the mass ratio of grinding balls to materials is 30:1, the grinding jar is sealed, and ball milling is performed for 40 minutes under N2 protection to obtain Ga 90 Co4.

[0037] Test Example 2 This test example tests the catalytic activity of the liquid alloy catalysts of Example 2 and Comparative Examples 3-4 as thermal catalytic ammonia synthesis catalysts, wherein the method for thermal catalytic ammonia synthesis is: 500 mg of the catalyst is loaded into one end of the U-shaped reaction tube with a sieve plate of a fixed-bed reactor for ammonia synthesis, the reaction temperature is fixed at 300°C, the reaction pressure is 3MPa, the molar ratio of N2:H2 is 1:3, the flow rate of the mixed gas is 120mL / min, the generated ammonia is collected and the ammonia yield is calculated (the ammonia yield calculation method is the same as that of Test Example 1), and the results are shown in Table 2.

[0038] Table 2 Test results of the catalytic reaction activity of synthetic ammonia in Example 2 and Comparative Examples 3-4

[0039] From the results in Table 2, it can be seen that compared with the single metal modified Ga liquid alloy Ga 94 Fe6 and Ga 90 Co4, bimetallic modified Ga liquid alloy Ga prepared in Example 2 90 Fe6Co4 has a good ammonia synthesis reaction rate and a significant improvement in activity.

[0040] Example 3 This embodiment provides a Ga-Fe based liquid alloy catalyst, and the preparation method thereof comprises the following steps: in a glove box filled with N2, 1.84 g of Ga powder, 0.08 g of Fe powder and 0.08 g of Mo are weighed and placed in a polytetrafluoroethylene grinding jar, the mass ratio of grinding balls to materials is 30:1, the grinding jar is sealed, and ball milling is performed for 20 minutes under N2 protection to obtain a Ga-Fe based liquid alloy catalyst Ga 92 Fe4Mo4.

[0041] Comparative Example 5 This comparative example proposes a liquid alloy catalyst, and its preparation method comprises the following steps: in a glove box filled with N2, 1.92g of Ga powder and 0.08g of Fe powder are weighed and placed in a polytetrafluoroethylene grinding jar, the mass ratio of grinding balls to materials is 30:1, the grinding jar is sealed, and ball milling is performed for 20 minutes under N2 protection to obtain Ga 96 Fe4.

[0042] Comparative Example 6 This comparative example proposes a liquid alloy catalyst, and its preparation method comprises the following steps: in a glove box filled with N2, 1.92g of Ga powder and 0.08g of Mo powder are weighed and placed in a polytetrafluoroethylene grinding jar, the mass ratio of grinding balls to materials is 30:1, the grinding jar is sealed, and ball milling is performed for 20 minutes under N2 protection to obtain Ga 96 Mo4.

[0043] Test Example 3 This test example tests the catalytic activity of the liquid alloy catalysts of Example 3 and Comparative Examples 5-6 as thermal catalytic ammonia synthesis catalysts, wherein the method for thermal catalytic ammonia synthesis is: 500 mg of the catalyst is loaded into one end of the U-shaped reaction tube with a sieve plate of a fixed-bed reactor for ammonia synthesis, the reaction temperature is fixed at 300°C, the reaction pressure is 3MPa, the molar ratio of N2:H2 is 1:3, the flow rate of the mixed gas is 120mL / min, the generated ammonia is collected and the ammonia yield is calculated (the ammonia yield calculation method is the same as that of Test Example 1), and the results are shown in Table 3.

[0044] Table 3 Test results of the catalytic reaction activity of synthetic ammonia in Example 3 and Comparative Examples 5-6

[0045] From the results in Table 3, it can be seen that compared with the single metal modified Ga liquid alloy Ga 96 Fe4 and Ga 96 Mo4, bimetallic modified Ga liquid alloy Ga prepared in Example 3 92 Fe4Mo4 has a good ammonia synthesis reaction rate and a significant improvement in activity.

[0046] In summary, the Ga-Fe-based liquid alloy catalyst of the present invention has good reaction activity at low temperature and low pressure, can reduce the energy consumption of the ammonia synthesis process, improve the efficiency of the ammonia synthesis reaction, and has good application prospects.

[0047] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0048] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A Ga-Fe based liquid alloy catalyst, characterized in that: The Ga-Fe-based liquid alloy catalyst includes metal Ga, metal Fe and metal M, and the metal M is one of Ti, Mn, Co, Ni, Cu, Zr, Nb, Mo, and W.

2. The Ga-Fe based liquid alloy catalyst according to claim 1, characterized in that: In the Ga-Fe-based liquid alloy catalyst, the mass percentage of the metal Ga is 90% to 99%; And / or, in the Ga-Fe based liquid alloy catalyst, the mass ratio of the metal Fe to the metal M is 1-2:

1.

3. A method for preparing a Ga-Fe based liquid alloy catalyst as claimed in any one of claims 1 to 2, characterized in that: It includes the following steps: Under a protective atmosphere, metal Ga powder, metal Fe powder and metal M powder are added into a ball milling jar and sealed, and ball milling is performed in a sealed state to obtain a Ga-Fe-based liquid alloy catalyst.

4. The method for preparing a Ga-Fe based liquid alloy catalyst according to claim 3, characterized in that: The ball-to-material ratio of the ball mill is 20-30:1, the rotation speed is 200-600 rpm, and the time is 10-60 min.

5. The method for preparing a Ga-Fe based liquid alloy catalyst according to claim 3, characterized in that: The protective atmosphere was in a N2 or Ar glove box.

6. The method for preparing a Ga-Fe based liquid alloy catalyst according to claim 3, characterized in that: The purity of the metal Ga powder and the metal Fe powder is 99.99%.

7. Use of the Ga-Fe based liquid alloy catalyst as claimed in any one of claims 1 to 2 in thermal catalytic synthesis of ammonia.

8. The use according to claim 7, characterized in that: It includes the following steps: The Ga-Fe-based liquid alloy catalyst is loaded on one end of the U-shaped reaction tube with a sieve plate of the fixed reaction bed for synthetic ammonia, and a mixed gas of N2 and H2 is introduced to heat the reaction.

9. The use according to claim 8, characterized in that: In the mixed gas, the molar ratio of N2 to H2 is 1:1-5, and the flow rate of the mixed gas is 20-300 mL / min.

10. The use according to claim 8, characterized in that: The temperature of the heating reaction is 200-500° C. and the pressure is 1-5 MPa.

Citation Information

Patent Citations

  • Process for the preparation of ammonia and ammonia synthesis catalyst

    CA2300520A1

  • Low-pressure synthesized ammonia catalyst and preparation method thereof

    CN105289624A

  • Method for catalytically synthesizing ammonia based on liquid alloy

    CN112250088A

  • Titanium dioxide loaded copper-gallium-indium liquid alloy catalyst and preparation method and application thereof

    CN113751010A

  • Synthetic ammonia catalyst loaded on surface of composite zirconate as well as preparation method and application of synthetic ammonia catalyst

    CN118416878A

Cited By

  • Alloy catalyst for integration of H2 storage and CO2 conversion and preparation method thereof

    CN121016768A